Dose-Response Relationship Between Oral Lutein Intake and Plasma Lutein Concentration: A Randomized Controlled Trial - Xiong, Ke; Zhao, Yanhui; Hu, Shouna; Ma, Aiguo; Ma, Yan (Frontiers in Nutrition, 2022)
Lutein was shown to provide health benefits for a few diseases. The dose-response relation of oral lutein intake in humans has rarely been reported. The objective is to investigate the dose-response relation between oral lutein intake and plasma lutein concentration in humans. Forty subjects were recruited from Qingdao University, China in 2014. The subjects were randomly divided into four groups: (1–3) consuming 10, 20, or 40 mg lutein by one, two, or four capsules of lutein A, respectively; (4) consuming 20 mg lutein by two capsules of lutein B (containing 280 mg n-3 fatty acid). After a single oral dose, plasma lutein concentrations were measured at 9-time points. The raise of plasma lutein concentration by a 40 mg dose was significantly higher than by a 10 or 20 mg dose. Plasma lutein concentrations were not significantly different between taking 20 mg lutein A and 20 mg lutein B. A dose-response relation was demonstrated between oral lutein administration and plasma lutein concentration. The dose-response relation was more pronounced among men. The current work provides a scientific basis for recommending a dietary intake level of lutein. Future work should validate the results in other ethnic and age groups.